2020
DOI: 10.1016/j.injury.2020.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Cause, treatment costs and 12-month functional outcomes of children with major injury in NSW, Australia

Abstract: Background: Information about children treated in New South Wales (NSW), Australia following major injury has been limited to those treated at trauma centres using mortality as the main outcome measure, restricting assessment of the effectiveness of the Trauma System. This study sought to describe the detailed characteristics as well as functional and psychosocial health outcomes of all children suffering major injury in NSW.Methods: A longitudinal study was conducted between July 2015 and November 2017 and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, it is essential not to forget the fact that people with scars due to acid attacks are first of all victims, which must be followed from a psychological point of view, even during treatments, given the strong emotional impact that aesthetic-functional recovery can have [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is essential not to forget the fact that people with scars due to acid attacks are first of all victims, which must be followed from a psychological point of view, even during treatments, given the strong emotional impact that aesthetic-functional recovery can have [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of injured children were males in both VEMD (56.2%) and Non-VEMD (58.8%) reporting hospitals ( Table 1 ); a considerably lower proportion than that reported by other Australian sources [ 4 , 23 , 24 ]. There were similar proportions of children injured in the toddler and child years, with an increase in teenage years: not dissimilar to other reports [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 85%
“…The present study, undertaken as part of the aforementioned larger longitudinal study, 5 included children who ultimately received definitive care at a NSW PTC, <16 years requiring ICU or an ISS ≥9 treated in NSW or who died following injury between July 2015 and September 2016. The 491 children identified via NSW PTCs, account for 79% of the longitudinal study cohort, and were included as their medical records were accessible.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of 625 children in New South Wales (NSW) sustaining major injury, there was no survival benefit for children receiving definitive care at a PTC. 5 However, peer review of a cohort children from the same study demonstrated an overall adverse event (AE) rate of 7.6%. Of these cases, 37% were determined to be a near miss that did not result in death, 15% preventable errors that resulted in lasting disability, and one case a near miss 6 of death.…”
Section: Introductionmentioning
confidence: 99%